Grindability and surface integrity of in situ TiB2 particle reinforced aluminum matrix composites. Issue 1 (January 2017) - Lin, Kunyang; Wang, Wenhu; Jiang, Ruisong; Xiong, Yifeng; Song, Guodong
Abstract In situ TiB2 particle-reinforced aluminum matrix composite (in situ TiB2 /Al composites) is a new kind of metal matrix composite. With in situ synthesis method, a better adhesion at interfaces is achieved and hence improves mechanical properties. However, few literature focused on its grindability and surface integrity which limited its widespread use in industries. In this paper, the effects of grinding parameters and grinding wheels on the grinding performance of in situ TiB2 /Al composites are investigated experimentally. The results show that the grinding performance is mostly affected by the wheel speed and grinding depth. The signal alumina wheel has the best grindability in grinding in situ TiB2 /Al composites. Unlike other ex situ PMMCs, the in situ TiB2 /Al composite is removed in a ductile-mode and pull-out or fractured particles are not found on the ground surface. Surface thermal softening effect and residual tensile stress indicate thermal effect dominate over mechanical effect in the grinding process. These results can be used to understand the material removal mechanism of grinding in situ TiB2 /Al composites.